Solução numérica das equações de Ginzburg-Landau dependentes do tempo: aplicações a materiais supercondutores mesoscópicos - Sardella, Edson [UNESP] (My University, 2018)
In the first part of this work we review the main aspects of classical field theory. Next, we apply this theory to the derivation of the London and Ginzburg-Landau equations. The phenomenological theories of superconductivity are discussed, where we determine the fundamental lengths, the coherence length and the London penetration depth. We also discuss the thermodynamic critical field for type I superconductors, and the lower and upper critical fields for type II superconductors. The Abrikosov vortex lattice for type II superconductors is also discussed. In the second part, we rewrite the time-dependent Ginzburg-Lanadu equations (TDGL) in terms of the auxiliary fields in order to satisfy the gauge invariance. The TDGL equations written in this form are then discretized using the link-variables method. In the last part, we apply the TDGL theory to superconductors of mesoscopic dimensions for the study of the state of vortices in confined systems.

Na primeira parte deste trabalho revisamos os principais aspectos da teoria clássica de campos. Em seguida, aplicamos esta teoria na derivação das equações de London e de Ginzburg-Landau. As teorias fenomenológicas da supercondutividade são discutidas, onde determinamos os comprimentos fundamentais de coerência e de penetração de London. Também discutimos o campo crítico termodinâmico para supercondutores do tipo I, e os campos críticos inferior e superior para os supercondutores do tipo II. A rede de vórtices de Abrikosov para supercondutores do tipo II também é aborda. Na segunda parte, reescrevemos as equações de Ginzburg-Lanadu dependentes do tempo (TDGL) em termos dos campos auxiliares com finalidade satisfazer a invariância de calibre. As equações TDGL escritas nessa forma são então discretizadas usando o método de variáveis de ligação. Na última parte, aplicamos a teoria TDGL para supercondutores de dimensões mesoscópicas para o estudo do estado de vórtices em sistemas confinados.
Numerical solution of the time dependent Ginzburg-Landau equations: applications to mesoscopic superconducting materials
Keywords: Superconductivity; Vortex; Mesoscopic; Kinematic vortex; TDGL equations; Supercondutividade; Vórtice; Mesoscópico; Vórtice cinemático; Equações TDGL